ANALISIS HAKIKAT IPA PADA BUKU SISWA KELAS IV SUB TEMA I TEMA 3 KURIKULUM 2013 - Ika Candra Sayekti; Ika Fajar Rini; Fawzia Hardiyansyah (Profesi Pendidikan Dasar, 2019)
This study was aim to analyse science as a process skill, products/content, and attitudes on students’ book at 4th grade Theme 3 Curriculum 2013. Tujuan penelitian ini yaitu untuk mengkaji penerapan hakikat IPA pada buku siswa kelas IV Tema 3 Kurikulum 2013. The design of this study was qualitative with the type of content study research. The data was collected through documentation. Data analysis techniques through reduction, presentation and drawing conclusions. The results showed that scence as a process skill, products/content and attutudes was available on that book, but the aspect of science process skill, science as product and science as hat attitudes was not complete. Science as a product/content found in this book merely on fact, concept, and principle. Science as attitudes found on this book are honest, opend minded, responsible, objective, cooperative, critical thinking, curiosity, careful, discipline, care for environment. Science as a process found of this book are still limited in: observing, classifying, concluding, and communicating.